2016
DOI: 10.1007/s00540-016-2211-4
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in critically ill patients

Abstract: Sarcopenia occurring as a primary consequence of aging and secondary due to certain medical problems including chronic disease, malnutrition and inactivity is a progressive generalized loss of skeletal muscle mass, strength and function. The prevalence of sarcopenia increases with aging (approximately 5-13 % in the sixth and seventh decades). However, data showing the prevalence and clinical outcomes of sarcopenia in intensive care units (ICUs) are limited. A similar condition to sarcopenia in the ICU, called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 63 publications
(63 reference statements)
1
99
1
12
Order By: Relevance
“…Sarcopenia can be classified as primary, meaning it is caused from aging itself, and as secondary from inactivity, certain diseases, medication, or malnutrition [21]. Skeletal muscle mass is known to decrease with age, mainly driven by DXA and BIA until now [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia can be classified as primary, meaning it is caused from aging itself, and as secondary from inactivity, certain diseases, medication, or malnutrition [21]. Skeletal muscle mass is known to decrease with age, mainly driven by DXA and BIA until now [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that muscle loss increases with sustained length of stay in the ICU, a condition known as ICU-acquired weakness that is related to inactivity in the ICU plus the hypermetabolic state of critically ill patients. 29,30 It is possible that the decrease in ICU days resulted in better daily activities (i.e., eating, bathing, dressing, toileting, and walking). 31 The 6MWT is a valid outcome in ICU survivors; it has been used in a prior ICU randomized controlled trial 32 and predicts patient-centered outcomes including mortality and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The overall picture of AA kinetics in the unfed critically ill catabolic patient is one of rapid protein turnover of muscle compartments to supply the splanchnic organs, primarily the liver for supporting gluconeogenesis, and the bone marrow, spleen, and lymph nodes to support immune function and immunoglobulin synthesis 15 , 23 , 24 . With this unidirectional flow of nitrogen substrate from muscle, it is not surprising that a large amount of data now supports the concept that poor outcomes result in a population of ICU patients with sarcopenia or low muscle mass (as demonstrated by axial imaging) 12 , 25 . A reduced lean body tissue to adipose ratio on axial imaging at the level of the third lumbar vertebra has been shown to adversely affect outcomes for colorectal, esophageal, and pancreatic cancer, as well as lymphoma and hepatoma 26 28 …”
Section: Protein Kinetics In the Icu—a Confusing Picturementioning
confidence: 99%